2021
DOI: 10.21873/anticanres.15162
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Sex Hormone Receptors in Head-and-neck Cancer? Links with HPV Infection and Prognosis

Abstract: Background/Aim: Head-and-neck squamous cell carcinoma (HNSCC) is the fifth most common cancer in the world and human papillomavirus (HPV) is an important risk factor for this neoplasm. Recent studies showed an association between sex hormone receptors and pathogenesis and/or prognosis in patients with HNSCC. The aim of this study was to clarify the expression patterns of sex hormone receptors in HPV-positive and HPV-negative HNSCC and their associations with tumour biopathology and biological behaviour. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 69 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…Other studies have suggested that estrogen could have a beneficial impact on survival after HNC [ 28 31 ], however that correlation was not analyzed here. In consistency with other studies [ 8 , 12 , 24 , 26 , 27 , 32 , 33 ], we saw that higher age and performance status correlated with an increased rate of early death.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested that estrogen could have a beneficial impact on survival after HNC [ 28 31 ], however that correlation was not analyzed here. In consistency with other studies [ 8 , 12 , 24 , 26 , 27 , 32 , 33 ], we saw that higher age and performance status correlated with an increased rate of early death.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested that estrogen could have a beneficial impact on survival after HNC [2225], however that correlation was not analyzed here. In consistency with other studies [8, 12, 18, 20, 21, 26, 27], we saw that higher age and performance status correlated with an increased rate of early death.…”
Section: Discussionmentioning
confidence: 99%
“…According to an analysis of scientific literature about sex hormone receptors in head and neck squamous cell carcinoma (HNSCC), ERα plays various roles in the biopathology of HNSCC, particularly oropharyngeal cancer. These include promoting DNA hypermutation, facilitating HPV integration, and cooperating with epithelial growth factor receptor (EGFR) [ 82 ]. This may explain the increased mortality of lip/oral/pharyngeal cancer in our study.…”
Section: Discussionmentioning
confidence: 99%